Classical, barrierless, and activationless discharge of palladium(II) iminodiacetate complexes - Kublanovsky, V.S.; Nikitenko, V.N. (Reports of the National Academy of Sciences of Ukraine, 2016)
The kinetic (exchange currents, apparent electron transfer coefficients) and energy (activation energy of diffusion and electron-transfer reaction) parameters of barrierless, ordinary (classic), and activationless discharge bis-iminodiacetate complexes of palladium(II) are determined. The actual and true activation energies and the latent heat of the electrode process are calculated.